Effect of Various Blansing Treatment and Drying Temperature on Organoleptic Characteristics of Mustard Leaf Stalk Flour (Brassica juncea) - Zendy Violita Rukmana; Ida Agustini Saidi (Procedia of Engineering and Life Science, 2021)
This study aims to determine the effect of blanching method and drying temperatures on organoleptik properties of mustard stalk flour. The study was conducted at the Development Product and Food Analysis Laboratory of Muhammadiyah Sidoarjo University from March to May 2020 used basic descriptive method. The sample used was mustard greens stalk. Various blanching method used without blanching, water blanching, steam blanching, and microwave blanching. Various temperature used cabinet drying at 55°C and 65 oC. The result showed there was different characteristic organoleptik of mustard stalk flour between blanching method and drying temperature. The best treatment was mustard stalk flour that used steam blanching and drying temperature 55 oC that show hedonic test of colour 3,47, texture 3,10, and aroma 2,43.